Maxillaria aureoglobula (Orchidaceae, Maxillariinae): A new record from Brazil - Engels, Mathias E.; Ferneda-Rocha, Lilien C. (Lankesteriana: International Journal on Orchidology, 2016)
We present the first record of Maxillaria aureoglobula from Brazil, found at Mato Grosso State, in Southern Amazon. A description, illustration, photos and comments about the species are provided.